2014
DOI: 10.1101/gr.177014.114
|View full text |Cite
|
Sign up to set email alerts
|

RSC-dependent constructive and destructive interference between opposing arrays of phased nucleosomes in yeast

Abstract: RSC and SWI/SNF are related ATP-dependent chromatin remodeling machines that move nucleosomes, regulating access to DNA. We addressed their roles in nucleosome phasing relative to transcription start sites in yeast. SWI/SNF has no effect on phasing at the global level. In contrast, RSC depletion results in global nucleosome repositioning: Both upstream and downstream nucleosomal arrays shift toward the nucleosome-depleted region (NDR), with no change in spacing, resulting in a narrower and partly filled NDR. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
131
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(152 citation statements)
references
References 60 publications
21
131
0
Order By: Relevance
“…AT-rich sequences upstream of transcribed sequences exclude nucleosomes because they are less capable of bending around a histone octamer 90,91 . Chromatin remodellers such as the RSC complex maintain these nucleosome-depleted regions (NDRs) by sliding nucleosomes away from this region 92,93 (FIG. 2b).…”
Section: Transcription Regulation By Histone Exchangementioning
confidence: 99%
“…AT-rich sequences upstream of transcribed sequences exclude nucleosomes because they are less capable of bending around a histone octamer 90,91 . Chromatin remodellers such as the RSC complex maintain these nucleosome-depleted regions (NDRs) by sliding nucleosomes away from this region 92,93 (FIG. 2b).…”
Section: Transcription Regulation By Histone Exchangementioning
confidence: 99%
“…Previous studies have reported that chromatin remodeling factors are responsible for the well positioned +1 and −1 nucleosomes at gene promoters and also for packing nucleosomes into organized arrays against these founding nucleosomes (Mavrich et al 2008; Gkikopoulos et al 2011;Zhang et al 2011;Ganguli et al 2014). However, the nature of the barriers and mechanism(s) through which these arrays are phased remain unclear (Hughes and Rando 2014).…”
Section: Sequence-directed Chromatin Remodeling Creates Phased Nucleomentioning
confidence: 99%
“…This allows individual assembly stages to be dissected, defined, and the role of individual factors deciphered. Current approaches involving in vivo removal or inactivation of one or a few nucleosome-related activities, for example chromatin remodeling enzymes, via genetic manipulation (Badis et al, 2008; Ganguli et al, 2014; Gkikopoulos et al, 2011; Hartley and Madhani, 2009; Ocampo et al., 2016; Parnell et al, 2008; van Bakel et al, 2013; Whitehouse et al, 2007; Yen et al, 2012) have proven insightful for identifying factors involved, their contribution, and their genomic binding locations. Critically, however, direct versus indirect roles are not readily apparent due to the ever-present complex milieu of cellular proteins, and so cannot identify the minimal set of components and core mechanisms that directly establish the primary structure of chromatin.…”
Section: Introductionmentioning
confidence: 99%